2010
DOI: 10.1073/pnas.1000142107
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the full-length Shaker potassium channel Kv1.2 by normal-mode-based X-ray crystallographic refinement

Abstract: Voltage-dependent potassium channels (Kv) are homotetramers composed of four voltage sensors and one pore domain. Because of high-level structural flexibility, the first mammalian Kv structure, Kv1.2 at 2.9 Å, has about 37% molecular mass of the transmembrane portion not resolved. In this study, by applying a novel normalmode-based X-ray crystallographic refinement method to the original diffraction data and structural model, we established the structure of full-length Kv1.2 in its native form. This structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
220
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(238 citation statements)
references
References 34 publications
10
220
1
3
Order By: Relevance
“…Because the gating pore residues are mostly hydrophobic across the tree of life, it is generally accepted that their hydrophobicity plays a major role in controlling VSD movement (17,21,38). However, we found that a hydrophobic side chain is only exclusively required for I237, whereas the size of the lateral chain is the critical parameter for S240, F244, and F290.…”
contrasting
confidence: 36%
See 3 more Smart Citations
“…Because the gating pore residues are mostly hydrophobic across the tree of life, it is generally accepted that their hydrophobicity plays a major role in controlling VSD movement (17,21,38). However, we found that a hydrophobic side chain is only exclusively required for I237, whereas the size of the lateral chain is the critical parameter for S240, F244, and F290.…”
contrasting
confidence: 36%
“…The Kv1.2 refined X-ray structure shows that the residue homologous to S240 faces the tip of the side chain of R4 in the depolarized conformation (Fig. 1A) (21). S240 is the only gating pore residue capable of participating in hydrogen bond interactions and is well conserved in the VSD among Kv channels.…”
Section: Vsd Parameters Correlate With Physicochemical Properties Of mentioning
confidence: 99%
See 2 more Smart Citations
“…4). This feature of the hBD2-Kv1.3 interaction interface suggests that the Kv1.3 channel S1-S2 linker likely forms an extended loop similar to the loop in Kv1.2, which was observed by normalmode-based x-ray crystallographic refinement (24) (Fig. 4).…”
Section: Discussionmentioning
confidence: 93%